Removal of Reactive Dye by Using Soybean Cake - Tanyıldızı, M. Şaban; Altundoğan, H. Soner (Fırat University, 2017)
In this study, soybean cake as an economic adsorbent was used to remove reactive dye from aqueous solution. Effect of initial pH, dose, contact time and particle size were studied. The selected conditions are 2, 100 mesh, 1 g/l and 30 min for initial pH, particle size, adsorbent dosage and contact time, respectively. The equilibrium data and kinetic data were analyzed for adsorption mechanism and characteristic. According to the results, second order kinetic model and Langmuir isotherm model are well fitted to the experimental data obtained for Reactive Black 5 (RB5) adsorption on soybean cake. The monolayer adsorption capacity values were calculated as 250and285.7 mgRB5/g for 20 and 60°C, respectively.

Bu çalışmada sulu ortamlardan reaktif boyar maddenin gideriminde ekonomik bir adsorbent olarak soyafasülyesi keki kullanıldı. Başlangıç pH’sı, doz, temas süresi ve tanecik boyutunun etkisi incelendi. Başlangıç pH’sı 2, tanecik boyutu -200 meshten geçen tanecikler, doz 1g/l ve temas süresi 30 dakika olarak belirlendi. Adsorpsiyon mekanizması ve karakterizasyonu adsorpsiyon denge verileri ile kinatik verileri kullanılarak incelendi. Soyafasülyesi küspesiyle rekatif siyah 5 boyar maddesinin adsorpsiyonu için yapılan deneylerden elde edilen deneysel sonuçlara göre ikinci dereceden yalancı kinetic model ve Langmuir isotherm modellerine uyduğu görüldü. Tek tabak adsorpsiyon kapasitesi 20 °C’de 250 mgRB5/g, 60°C’de 285.7 mgRB5/g olarak bulundu.
Soyafasulyesi Küspesiyle Reaktif Boya giderimi